How Does Socioemotional Wealth in Business Families Contribute to Implementing Protocols? The Moderating Effect of the Generational Stage - Sánchez, Benjamin; Rodríguez, Maribel; Pérez, Leonor M. (European Journal of Family Business, 2025)
Drawing on team theory based on the input-process-outcome (IPO) perspective, this study analyses the impact of socioemotional wealth dimensions (input) on the implementation of family protocols (outcome) in business families. These protocols necessarily involve communication and decision-making processes. Specifically, the study examines the influence of family members' emotional attachment to and identification with the company through intrafamily succession on protocol implementation, considering the generational stage as a moderating factor. Based on a sample of 244 Spanish business families, the results reveal that the dimensions of socioemotional wealth contribute to the implementation of a protocol in second-generation business families.